2006
DOI: 10.1038/ncb1366
|View full text |Cite
|
Sign up to set email alerts
|

GM130 and GRASP65-dependent lateral cisternal fusion allows uniform Golgi-enzyme distribution

Abstract: The mammalian Golgi apparatus exists as stacks of cisternae that are laterally linked to form a continuous membrane ribbon, but neither the molecular requirements for, nor the purpose of, Golgi ribbon formation are known. Here, we demonstrate that ribbon formation is mediated by specific membrane-fusion events that occur during Golgi assembly, and require the Golgi proteins GM130 and GRASP65. Furthermore, these GM130 and GRASP65-dependent lateral cisternal-fusion reactions are necessary to achieve uniform dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

33
415
6
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 304 publications
(455 citation statements)
references
References 42 publications
33
415
6
1
Order By: Relevance
“…Significantly, the Golgi ribbon was disrupted in cells that lacked GRASP55 staining. The observed phenotype was similar to that previously noted after GM130 or GRASP65 knockdown (Puthenveedu et al, 2006), and quantification using the same image analysis protocol indicated a similar degree of Golgi fragmentation ( Figure 1C). The analysis was then carried out for cells arrested at late G2 phase of the cell cycle when the ribbon undergoes MEKdependent unlinking (Feinstein and Linstedt, 2007).…”
supporting
confidence: 84%
See 4 more Smart Citations
“…Significantly, the Golgi ribbon was disrupted in cells that lacked GRASP55 staining. The observed phenotype was similar to that previously noted after GM130 or GRASP65 knockdown (Puthenveedu et al, 2006), and quantification using the same image analysis protocol indicated a similar degree of Golgi fragmentation ( Figure 1C). The analysis was then carried out for cells arrested at late G2 phase of the cell cycle when the ribbon undergoes MEKdependent unlinking (Feinstein and Linstedt, 2007).…”
supporting
confidence: 84%
“…In contrast, fluorescent Golgi objects in GRASP55-depleted cells, even when they seemed optically contiguous, failed to recover significantly from photobleaching. These results were quantified for multiple experiments ( Figure 2B), and representative movies are present in Supplemental Figure S1 and S2 movies.An earlier study found that disruption of the Golgi ribbon correlated with discontinuities in Golgi enzyme distribution and perturbed sialylation, resulting in an increase in nonsialylated proteins detectable on the cell surface (Puthenveedu et al, 2006). This was also the case for cells exhibiting an unlinked Golgi due to GRASP55 depletion.…”
mentioning
confidence: 81%
See 3 more Smart Citations